On the Question of the Imperative or Dispositivity of the Norm of Paragraph 1 of Article 782 of the Civil Code of the Russian Federation, Which Establishes the Right of the Customer to Unmotivated Refusal of the Contract for the Provision of Paid Services - S. V. Markin (Теоретическая и прикладная юриспруденция)
In this article, the author explores the question of the qualification of Paragraph 1 of Article 782 of the Civil Code of the Russian Federation, which gives the right to unmotivated refuse to perform a contract for the provision of paid services. The paper considers various approaches to the issue of dispositivity or imperativeness of this norm. The positions of scientists on the legal nature of 782 of the Civil Code of the Russian Federation are considered. The author analyzes judicial practice for the possibility of blocking the right to unilateral refusal. Based on the presented analysis, conclusions are drawn about the dispositivity of 782 of the Civil Code of the Russian Federation regarding the inadmissibility of blocking the right to unilateral refusal itself, at the same time, the parties are allowed to establish a different procedure for the implementation of this right. A possible option for improving domestic legislation regulating the termination of a contract for the provision of paid services is also proposed.